2020
DOI: 10.1016/j.fsigen.2019.102151
|View full text |Cite
|
Sign up to set email alerts
|

Validation of NGS for mitochondrial DNA casework at the FBI Laboratory

Abstract: As a first step towards integrating next generation sequencing (NGS) technology into the FBI Laboratory's operational casework, the PowerSeq™ CRM Nested System, an NGS-based mitochondrial DNA (mtDNA) control region assay, was developmentally and internally validated. The validation studies were conducted in accordance with the Scientific Working Group on DNA Analysis Methods (SWGDAM) Validation Guidelines for Forensic DNA Analysis Methods, and the FBI's Quality Assurance Standards (QAS) for Forensic DNA Testin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 51 publications
1
34
0
Order By: Relevance
“…This is why quantitation of the mtDNA and the nDNA in a sample to direct the input quantity for mitogenome PCR may be important in mini amplicon laboratory workflows (e.g., [79,80]), or those involving high-quality DNA followed by WGS or hybridization capture. Validation studies have demonstrated that mini amplicon strategies require mtDNA amounts as little as the equivalent of a single cell or even less as template to generate reliable sequences [81], and, as little as 23 copies of mtDNA to generate a full mitogenome sequence [47]. This indicates that smaller amounts of template mtDNA are sufficient for mitogenome sequencing.…”
Section: Numts In Forensic Applicationsmentioning
confidence: 99%
“…This is why quantitation of the mtDNA and the nDNA in a sample to direct the input quantity for mitogenome PCR may be important in mini amplicon laboratory workflows (e.g., [79,80]), or those involving high-quality DNA followed by WGS or hybridization capture. Validation studies have demonstrated that mini amplicon strategies require mtDNA amounts as little as the equivalent of a single cell or even less as template to generate reliable sequences [81], and, as little as 23 copies of mtDNA to generate a full mitogenome sequence [47]. This indicates that smaller amounts of template mtDNA are sufficient for mitogenome sequencing.…”
Section: Numts In Forensic Applicationsmentioning
confidence: 99%
“…The CE-based Sanger sequencing system, although limited in its ability to sequence large expanses of the mtGenome on a practical level, has been demonstrated to be highly reliable. However, with the development and maturation of massively parallel sequencing (MPS) technologies [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ], there is interest in enhancing mtDNA analysis, with some laboratories already tackling the validation and implementation process [ 20 , 21 , 22 , 23 , 24 ]. Analysis of the mtGenome offers a good first step to transition MPS workflows as current CE-based workflows are already sequence-based, making data analysis of MPS results a more familiar and similar process.…”
Section: Introductionmentioning
confidence: 99%
“…MPS makes it feasible to sequence the entire mtGenome with less labor, less sample consumption, and an overall lower cost per nucleotide. Furthermore, MPS provides an increase in sensitivity over currently-used CE-based technologies allowing for detection and characterization of lower-level heteroplasmies [ 20 , 24 , 25 , 26 ]. Additionally, the increase in information, provided by evaluating the entire mtGenome, offers the potential for an increase in discrimination power and phylogenetic resolution [ 10 , 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, the issue on apparent heteroplasmy in mitochondrial data and data interpretation was addressed by several studies (Bandelt and Salas 2012;He et al 2010;Ye et al 2014;Just et al 2014) resulting in a comprehensive review on the quality of mtDNA data derived from sequencing studies (Just et al 2015) . It has been shown that certain studies can overestimate the presence of heteroplasmy, which can often be explained by external or cross-contamination (Yao et al 2007;Just et al 2014Just et al , 2015Brandhagen et al 2020;Yin et al 2019) , artificial recombination (Bandelt et al 2004) , artifacts, index hopping (Van Der Valk et al 2019) or analysis software inconsistencies. Sample contamination is still a major issue in both nuclear DNA (nDNA) and mtDNA sequencing studies that must be prevented to avoid mistakes as it occurred with Sanger sequencing studies in the past (Salas et al 2005) .…”
Section: Introductionmentioning
confidence: 99%